Parenting Self Efficacy pada Orang Tua dengan Tuna Netra - Mafaza Mafaza; Nila Anggreiny; Halfizh Alfara (Jurnal Ilmu Perilaku, 2017)
This research aims to explore significant description and factors that influence parenting self efficacy toward blind parents with middle childhood children. This research basically applies phenomenology qualitative method. The subject of this research focuses on two couples of blind parents who live with their middle childhood children. The data collection is conducted by applying the interview and observation. All responses were analysed with Van Kaam phenomenology method which has been modified by Moustakas (1994). Parenting self efficacy of the four informant shows great value on domain nurturance, however it shows less value on domains of discipline and recreation. There are various factors that affect parenting self efficacy on these subjects, such as limitation of eyesight, childhood experience, culture and community, experience with children, cognitive level, sociomarital support, and busy hours. Besides, number of children, economy, and children’ severe disease can also be influential factors of parenting self efficacy.